Solitary cutaneous neoplasms: analysing the uncertain behaviour with the aid of histopathology - Lekkala Sreedevi; D. Edukondala Rao; A. Vijaya Kumari; Machani Niharika; P. Sravani; V. Sivasankara Naik (Клиническая практика, 2024)
BACKGROUND: Skin tumours can be classified as either benign or malignant, resulting due to the proliferation of one or more components of the skin. Reportedly, there has been a rise in the prevalence of skin cancer in recent decades, which has led to rely on histological evidence to distinguish between various types of skin cancer.